2007
DOI: 10.1177/1742395307085335
|View full text |Cite
|
Sign up to set email alerts
|

The biographical impact of teenage and adolescent cancer

Abstract: While recognizing the potentially devastating impact of cancer at any age, the research findings suggest a distinct effect in adolescence and young adulthood resulting from a disrupted biography at a critical transitional moment in the life trajectory that can have a chronic effect after the acute stage of the illness is passed. An age-appropriate approach to the care of young people with cancer that takes into account the distinct effects of life stage in this age-group can mitigate the negative impact on lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
131
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(146 citation statements)
references
References 13 publications
(11 reference statements)
11
131
0
4
Order By: Relevance
“…This is because social forces often obscure and mute their suffering. Stage of life and timing of the illness during the life course has also been found to influence the extent to which an individual experiences illness as biographical disruption (Grinyer, 2007;Wilson, 2007). Thus, these challenges and qualifications suggest that universal prescriptions of chronic illness as biographical disruption cannot be justified.…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…This is because social forces often obscure and mute their suffering. Stage of life and timing of the illness during the life course has also been found to influence the extent to which an individual experiences illness as biographical disruption (Grinyer, 2007;Wilson, 2007). Thus, these challenges and qualifications suggest that universal prescriptions of chronic illness as biographical disruption cannot be justified.…”
Section: The Importance Of Contextmentioning
confidence: 99%
“…However, few studies have explored patients' perceptions of wellness post-transplant and how these perceptions may change over time. Patient narratives are considered to offer a powerful tool for understanding biomedical reality in terms of illness experience and its social and cultural context (1)(2)(3)(4)(5). The specificities of kidney transplantation pose something of a problem for a narrative approach to analyzing patients' experiences after the transplant.…”
Section: Transplant Patients Introductionmentioning
confidence: 99%
“…A recent systematic review on this subject subdivides adolescents and young adults into three groups based on social needs. 45 The review found that mid-adolescents (15-17 years old) are principally coping with the physical changes of puberty and the formation of a social identity, 46 whereas emerging adults (18-25 years old) are often in the process of leaving their childhood home, obtaining higher education, and establishing social connections independent from childhood.…”
Section: Psychosocial Effectsmentioning
confidence: 99%
“…48 This may be associated with specific treatment side effects such as alopecia. 46 Any cognitive problems related to treatment may also hinder acquisition of social skills and lead to further problems with self esteem. 49 …”
Section: Social Effectsmentioning
confidence: 99%